The Effect of Guided Imagery Techniques on Elderly Blood Pressure Hypertension in South Purwokerto - Utami, Mega Putri; Siwi, Adiratna Sekar; Khasanah, Suci (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: Hypertension has become a leading cause of death globally, often referred to as